A Study on the Impact of Diabetes Mellitus on the Severity of COVID-19-Associated Mucormycosis - Madan, Siddharth; Dutta, Shelly; Yadav, Rekha; Rohatgi, Jolly; Bajaj, Ishita; Tadu, Nampi; Sharma, Rahul; Das, Gopal Krushna; Sahu, Pramod Kumar; Gupta, Neelima (Annals of the National Academy of Medical Sciences (India), 2023)
Objectives: Diabetes mellitus (DM) seems the most common predisposing factor for rhino-orbito-cerebral mucormycosis (ROCM). This study aimed to study the impact of DM on the severity of COVID-19-associated ROCM (CAM).Methods: This was a retrospective analytical study performed over a period of 3 months to assess the impact of DM on the severity of CAM in 100 patients and association of clinical correlates of DM with severity of CAM.Statistical analysis: The data collected using the study tools were converted into a computer-based spreadsheet and analyzed. The statistical analysis comprised a descriptive analysis that involved calculating means, standard deviations, and proportions. For calculating the significance of the difference of mean between two groups, Student's t-test was applied. In addition, chi-square test (or Fisher's t-test if applicable) was applied to study the significance of association of clinical correlates of DM with severity of CAM for categorical variables and t-test for continuous variables.Results: The prevalence of DM was 67%. The average presenting blood sugar level was 245.9 ± 99.86 mg%. Glycated hemoglobin level between 4.5 and 6.5% was observed in 57 patients and over 6.5% in 43 subjects. A high body mass index (BMI) of 25 and above was noted in 52 patients. A significantly higher level of presenting blood sugar and a longer duration of hospital stay was noted in patients having stage 3b or higher (p < 0.05) when compared with those having stage 3a or below. No significant correlation was observed in patients in stage 3a or below and those presenting with stage 3b or higher in terms of BMI, waist to hip ratio, or total cholesterol levels. There was a strong correlation between blood sugar level at presentation, severity of DM with the severity of ROCM, and a strong inverse correlation noted between HDL level and severity of ROCM.Conclusion: A poor metabolic control is associated with a higher risk of a severe disease with intracranial involvement.
Keywords: ROCM; COVID-19; orbital mucormycosis; diabetes mellitus; corticosteroids